2014
DOI: 10.1177/0886260514549466
|View full text |Cite
|
Sign up to set email alerts
|

Explicating the Role of Sexual Coercion and Vulnerability Alcohol Expectancies in Rape Attributions

Abstract: Despite evidence suggesting that alcohol expectancies may influence people's rape perceptions, no study to date has measured context-specific expectancies comprehensively. This study represents an initial investigation of the role of sexual coercion and vulnerability alcohol expectancies in young Australian adults' rape blame attributions. Using a vignette method, it was hypothesized that participants' stronger expectancy endorsement would predict lesser perpetrator blame and greater victim blame. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Research clearly supports a positive relationship between endorsement of rape myths and victim blaming in acquaintance rape cases (Lonsway and Fitzgerald, 1994; Stormo et al, 1997; Schuller and Wall, 1998; Varelas and Foley, 1998; Frese et al, 2004; Hayes-Smith and Levett, 2010; Masser et al, 2010; Basow and Minieri, 2011; Hammond et al, 2011; Romero-Sánchez et al, 2012; McKimmie et al, 2014; Starfelt et al, 2015; Qi et al, 2016; Persson et al, 2018). Additionally, the relationship between rape myth endorsement and greater victim blame tends to be strongest among men (Lonsway and Fitzgerald, 1994; Hayes-Smith and Levett, 2010; Hammond et al, 2011).…”
Section: Resultsmentioning
confidence: 86%
“…Research clearly supports a positive relationship between endorsement of rape myths and victim blaming in acquaintance rape cases (Lonsway and Fitzgerald, 1994; Stormo et al, 1997; Schuller and Wall, 1998; Varelas and Foley, 1998; Frese et al, 2004; Hayes-Smith and Levett, 2010; Masser et al, 2010; Basow and Minieri, 2011; Hammond et al, 2011; Romero-Sánchez et al, 2012; McKimmie et al, 2014; Starfelt et al, 2015; Qi et al, 2016; Persson et al, 2018). Additionally, the relationship between rape myth endorsement and greater victim blame tends to be strongest among men (Lonsway and Fitzgerald, 1994; Hayes-Smith and Levett, 2010; Hammond et al, 2011).…”
Section: Resultsmentioning
confidence: 86%
“…Another possibility is that alcohol expectancies, or stereotypic beliefs about the effects of alcohol, may be an important variable for attributions about alcohol-facilitated rape. In fact, recent research demonstrated that the expectancy that alcohol makes one sexually coercive was associated with higher victim and lower perpetrator blame, and these beliefs were predictive of blame over and above gender ideology variables (Starfelt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings with other gender ideology variables, men endorse greater rape myths than women; however, the relationship between gender and victim blame is mediated by rape myth acceptance (van der Bruggen & Grubb, 2014). In general, individuals who endorse high levels of rape myths are more likely to attribute blame and responsibility to a victim, endorse higher credibility to a perpetrator, and perceive lower responsibility for a perpetrator relative to those with lower levels of rape myths (Basow & Minieri, 2011; Kopper, 1996; Mason, Riger, & Foley, 2004; Newcombe, Van den Eynde, Hafner, & Jolly, 2008; Starfelt, Young, White, & Palk, 2015). In addition, compared with individuals with low rape myth acceptance, those with high rape myth acceptance demonstrate a tendency to minimize the assault experience and are less likely to believe that a rape has occurred, including a lower likelihood of convicting a perpetrator (Burt & Albin, 1981; Mason et al, 2004; Newcombe et al, 2008; Schuller & Wall, 1998).…”
Section: Observer Characteristicsmentioning
confidence: 99%
“…These double standards are evident in discourses on alcohol and intoxication in relation to rape and sexual assault in the NTE whereby women are ascribed blame and are responsibilized for their sexual assault if they are drunk, while men are exonerated for perpetrating sexual violence if intoxicated. This sexual double standard is evidenced in media representations (Gunby et al, 2013; Meyer, 2010), public perceptions (Starfelt et al, 2015), in mock jury debates (Finch & Munro, 2005), and in public safety campaigns which oblige women to regulate themselves to stay safe from men, rather than focusing on men’s aggressions (Brooks, 2011; Campbell, 2005). Indeed, there is a large body of scholarship in the United Kingdom and beyond on intoxication and women’s safety in the NTE which documents the gendered risk of navigating the NTE (Brooks, 2011; Griffin et al, 2009, 2013; Tan, 2013).…”
Section: Intoxication and Gendered Risk In The Ntementioning
confidence: 99%